Non-requirement of a regulatory subunit of Protein Phosphatase 2A, PP2A-B', for activation of Sex comb reduced activity in Drosophila melanogaster. - Moazzen, H.; Rosenfeld, R.; Percival-Smith, A. (Mechanisms of Development, 2009)
The Drosophila HOX transcription factor, Sex combs reduced (SCR), is required for determining labial and the first thoracic segmental identity. A Protein Phosphatase 2A holoenzyme assembled with the PP2A-B' regulatory subunit is proposed to specifically interact with, and dephosphorylate, the SCR homeodomain activating SCR protein activity. To test this hypothesis further, a null mutation was created in the PP2A-B' gene, PP2A-B'(Delta), using Flip-mediated, site-specific recombination. The number of sex comb bristles, salivary gland nuclei and pseudotracheal rows are SCR-dependent and were counted as a measure of SCR activity in vivo. Adults and larvae homozygous for PP2A-B'(Delta) showed no decrease in SCR activity. In addition, no evidence of functional redundancy of PP2A-B' with other regulatory subunits, Twins (TWS) and Widerborst (WDB), for dephosphorylation and activation of SCR activity was observed. In conclusion, a PP2A holoenzyme containing the PP2A-B' regulatory subunit has no role in the dephosphorylation and activation of SCR, and analysis of functional redundancy of PP2A regulatory subunits uncovered no evidence supporting a role of PP2A activity in dephosphorylation and activation of SCR.